Relationship of fatigue severity with pain level, obesity indices and functional performances in women with knee osteoarthritis - Justine, Maria; Shaari, Ida Hasni; Azizan, Azliyana; Mirza, Fatim Tahirah; Manaf, Haidzir (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
Knee osteoarthritis (KOA) is a common condition among women with obesity, affecting their musculoskeletal system. The pain experienced in KOA can hinder daily activities, leading to fatigue and reduced motivation to engage in meaningful tasks. This study aimed to explore the relationship between pain levels, obesity indicators, functional performance, and fatigue severity in women with KOA. This cross-sectional study recruited women aged 40 to 65 diagnosed with unilateral KOA and referred for physiotherapy management. Measurements included fatigue severity using the Fatigue Severity Scale, pain intensity using the Numerical Rating Scale, and obesity indicators such as body mass index (BMI), body fat percentage, and waist circumference. Functional performance was assessed through handgrip strength, the 5 Times Sit-to-Stand Test, the Timed Up and Go Test, the 6-Minute Walk Test and quality of life (QoL) using the WOMAC questionnaire. A total of 96 women (mean age = 54.76 years, SD = 5.54) participated in the study, with an average fatigue severity score of 34.51 (SD = 14.03). Participants with lower fatigue levels experienced less intense pain, lower body fat, and better QoL. Simple linear regression showed significant associations between fatigue severity and pain intensity (β = 4.089, p < 0.001), body fat percentage (β = 0.825, p < 0.001), and QoL (β = 0.304, p < 0.001). Pain management targeted weight reduction, and personalized exercise programs are essential in addressing fatigue in women with KOA. Further research with larger samples is recommended to better understand the dynamic relationship between pain, obesity, and fatigue.